An interquartile relationship between polyherbal extract based lozenges linkus a phase IV comparative randomised control trial - Rehman, Hina; Ali, Syed Adnan; Naveed, Safila; Usmanghani, Khan (Pakistan journal of pharmaceutical sciences, 2017)
The aim of the study is to determine the efficacy of polyherbal linkus with the other pharmaceutical marketed syrup having Acefyllin Piperazine, Diphenhydramine group and Aminophylline Diphenhydramine group on the basis of interquartile ranges on children. It was open label multi centric randomize control trial. The study was conducted on different private schools of East and West Malir, Karachi Pakistan with the special approval from the school's honors .informed consent and assents were taking before the enrollment of the study subjects .The study enrolled participants were 147 who evaluate on cough. Participants were divided into 3 interventional group according to the treatment regimen .One group of participant received Linkus Syrup however the 2nd group received Acefyllin Piperazine and 3rd group received Aminophylline Diphenhydramine group. The frequency of the cough on linkus syrup was considered to be achieved on the basis of interquartile relationship and impact has been observed on child and parent sleep and found significant (p <0.01).Poly herbal Linkus Syrup has the significant impact on cough frequency and associated problem on children and parent's sleep with minimum side effects (p<0.01) however the pharmacological treatments are considered to be more unwanted effects on human subjects.